(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2015)
Pile foundation is widely subjected to both vertical and lateral loads. The available design procedure assumes that the effect of these two loads is independent of each other and hence the pile design is carried out separately for vertical and lateral loads. The traditional methods for analysis of piles according to sub-grade reaction methods also do not consider the effect of interaction between the different load directions. The effect of combination vertical loads and lateral on pile performance that installed in cohesionlesssoils is considered in this paper through three-dimensional finite element analyses. In the numerical model, the pile was treated as a linear elastic material and the soil was idealized using the Mohr-Coloumb constitutive model. The results from the analysis of single piles under combined vertical and lateral loads are studied in this paper. The influences of related parameters such as shear strength (angle of internal friction and dilatation angle) of soil in term of loose and dense sands and pile/soil interface friction coefficient have also been studied in this work.The results have shown that the combination vertical load and lateral has a significant effect on the pile performance that installed in cohesionless soil.